Signs and symptoms in relation to progression, experiences of an uncertain illness situation in men with metastatic castration‐resistant prostate cancer—A qualitative study. (12th April 2022) - Rönningås, Ulrika; Holm, Maja; Doveson, Sandra; Fransson, Per; Beckman, Lars; Wennman‐Larsen, Agneta
Abstract: Objective: Signs and symptoms are important in monitoring prostate cancer, but there is a lack of understanding about the men's interpretation of signs and symptoms in relation to disease progression in advanced phases of the disease. The aim was to illuminate the experience of signs and symptoms in relation to disease progression in men with metastatic castration‐resistant prostate cancer (mCRPC). Method: Thirty longitudinal interviews were conducted with 11 men undergoing life‐prolonging treatment for mCRPC. Conventional content analysis was used. Results: The results illuminate an uncertainty that the men experience when interpreting signs and symptoms. The overarching theme was The experience of an uncertain illness situation within the framework of progression, with four subthemes: Symptoms triggering thoughts about disease progression ; Making sense of signs, also in the absence of symptoms ; Making sense of symptoms during treatment ; Progression triggering thoughts about the remainder of life . Conclusion: In the uncertain illness situation, the men strive to make sense of signs and symptoms based on previous experiences and in relation to disease progression. Understanding the men's perspectives on signs and symptoms in this late phase may help health care professionals communicate about disease progression considering the balance between treatment outcome and quality of life.